Pengaruh Enterprise Risk Management, Financial Distress, Kepemilikan Manajerial, dan Koneksi Politik Terhadap Integritas Laporan Keuangan - Esti Tita Setiadi; Rosiyana Dewi (Peneliti.net, 2023)
This study aims to analyze the effect of Enterprise Risk Management, Financial Distress, The Managerial Ownership and Political Connections on Integrity Financial Statment. The data used is secondary data obtained from the Indonesia Stock Exchange. The sampling technique used was a purposive sampling approach, namely the sampling method was based on certain criteria set by the researcher as an objective. The analitical method to test the data in this study used multiple panel data regression analysis using the Eviews. The poThis study uses non-cyclical cunsumer subsektor companies listed on the Indonesia Stock Exchange for the 2018-2021 period totaling 132 samples. The results of hypothesis testing conducted in this study indicate that Enterprise Risk Management have a positive effect on Integrity Financial Statment, Financial Distress have a negative effect on Integrity Financial Statment, The Managerial Ownership have a positive effect on Integrity Financial Statment, and Political Connections have no effect on Integrity Financial Statment.